2012
DOI: 10.1007/s11663-012-9701-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Slag Composition on the Distribution Behavior of Pb between FetO-SiO2 (-CaO, Al2O3) Slag and Molten Copper

Abstract: The distribution behavior of Pb between molten copper and Fe t O-SiO 2 (-CaO, Al 2 O 3 ) slags was investigated at 1473 K (1200°C) and p O 2 ¼ 10 À10 atm in view of the reaction mechanism of Pb dissolution into the slag. Furthermore, the lead capacity of the slag was estimated from the experimental results. The distribution ratio of Pb (L Pb ) decreases with increasing CaO content (~6 mass pct) irrespective of Fe/SiO 2 ratio (1.4 to 1.7). However, the addition of alumina into a slag with Fe/SiO 2 = 1.5 linearl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(5 citation statements)
references
References 33 publications
(50 reference statements)
0
5
0
Order By: Relevance
“…The variance trend of the influence of Al 2 O 3 content on both the critical cooling rate and crystallization temperature of the mold flux indicates that the Al 2 O 3 has an amphoteric effect on the continuous cooling crystallization behavior of the mold flux. In fact, the Al 2 O 3 is a typical amphoteric oxide, [28,29] and the amphoteric mechanism of Al 2 O 3 in molten slag is schematically shown in Figure 9. When Al 2 O 3 is added to acidic slag, it will work as a basic oxide to offer the O 2À and break the Si-O-Si bond, then increase the amount of non-bridging oxygen in the molten slag, consequently simplifying the silicate structure.…”
Section: A the Effect Of Al 2 O 3 Content On Continuous Cooling Crysmentioning
confidence: 99%
“…The variance trend of the influence of Al 2 O 3 content on both the critical cooling rate and crystallization temperature of the mold flux indicates that the Al 2 O 3 has an amphoteric effect on the continuous cooling crystallization behavior of the mold flux. In fact, the Al 2 O 3 is a typical amphoteric oxide, [28,29] and the amphoteric mechanism of Al 2 O 3 in molten slag is schematically shown in Figure 9. When Al 2 O 3 is added to acidic slag, it will work as a basic oxide to offer the O 2À and break the Si-O-Si bond, then increase the amount of non-bridging oxygen in the molten slag, consequently simplifying the silicate structure.…”
Section: A the Effect Of Al 2 O 3 Content On Continuous Cooling Crysmentioning
confidence: 99%
“…The sulfide capacity C s 2À was also calculated using the FactSage TM 7.3 software, [20,21] a commercial thermochemical computing package which has been widely used to obtain the equilibria of multicomponent, and multiphase metallurgical systems. [22][23][24][25][26][27][28][29][30][31] The effect of the different TiO 2 content and C/A ratio on C s 2À can be compared and the calculation results are plotted as iso-capacity contours in Figure 4. It can be easily found that the iso-capacity contours exhibit nearly the same tendency with the iso-a CaO contour in the present slag system: i) Sulfide capacity strongly dependent on the CaO content, ii) Sulfide capacity contours are parallel to the CaO saturation liquidus line, iii) Effect of TiO 2 content on sulfide capacity is less significant than that of…”
Section: Resultsmentioning
confidence: 99%
“…The schematic diagram of the experimental apparatus is shown in previous articles. 17,18) The slag (7.0 g) and SiMn alloy (3.5 g) were held in graphite crucibles under a CO atmosphere to equilibrate. For reducing removal of phosphorous under a very low oxygen potential, CO gas was diluted with Ar, which was purified using silica gel also in addition to Mg turnings at 723 K. The oxygen partial pressure can be calculated based on the following reaction: 19) ... With a CO/(CO + Ar) ratio of 0.25, the oxygen partial pressure is about 1.7 × 10 -17 atm at 1 823 K. The CO gas was passed through Drierite (W. A. Hammond Drierite Co. Ltd., Xenis, OH), Mg(ClO4)2, silica gel, and soda lime to eliminate moisture and impurities.…”
Section: Methodsmentioning
confidence: 99%